Pengaruh Kualitas Layanan Jasa terhadap Word Of Mouth dengan Kepuasan Pelanggan sebagai Variabel Antara (Studi pada Biro Perjalanan Umum Rosalia Indah Surabaya) - Deasy Prameswari; Anik Lestari Andjarwati (BISMA (Bisnis dan Manajemen), 2018)
Competition services company that happens in the present, especially the transport service which is services sectors that are consumed and have a huge impact on economic growth. To be able to withstand the competition, the company must continue to fix themselves to improving the quality of services to create customer satisfaction. One of the advantages which can be obtained by the company if the customer experience is the customer satisfaction will do the word of mouth. This study is conclusive research. The population in this study is the customer of General Travel Bureau Rosalia Indah Surabaya minimum 16 years old and have been using the services General Travel Bureau Rosalia Indah Surabaya at least twice. Samples taken as many as 158 people with accidental sampling technique. The measurement used is the questionnaire, and data were analyzed by Structural Equation Modeling. The results showed that the effect of variable services quality to customer satisfaction General Travel Bureau Rosalia Indah Surabaya amounted to 33.9%. The effect of variable customer satisfaction General Travel Bureau Rosalia Indah Surabaya against the word of mouth for 52.5%.